2010
DOI: 10.1590/s0037-86822010000600018
|View full text |Cite
|
Sign up to set email alerts
|

Hanseníase no Município de Buriticupu, Estado do Maranhão: busca ativa de casos na população adulta

Abstract: The high detection coefficient defines the town of Buriticupu, MA, as hyperendemic for leprosy. Active cases search is an important method for disease control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 4 publications
(6 reference statements)
3
13
1
8
Order By: Relevance
“…The SALSA scale results showed that most respondents had no activity limitations, which differed from the findings of Ikehara et al 24 . Cases with scores reflecting no limitations were the most frequent, followed by cases with scores reflecting mild limitations, a result similar to that reported by Silva et al 25 .…”
Section: Discussionsupporting
confidence: 90%
“…The SALSA scale results showed that most respondents had no activity limitations, which differed from the findings of Ikehara et al 24 . Cases with scores reflecting no limitations were the most frequent, followed by cases with scores reflecting mild limitations, a result similar to that reported by Silva et al 25 .…”
Section: Discussionsupporting
confidence: 90%
“…Another study, conducted in the city of Buriticupu (MA), also reported a higher rate of female leprosy patients 14 . However, there are studies 15,16 that found a higher percentage of males. It has been suggested that the biggest concern with body image and specific policies for the female population would justify the predominance of females 14 .…”
Section: Discussionmentioning
confidence: 97%
“…In 2011, a high detection rate of 15.88/100,000 inhabitants was registered in Brazil, according to parameters of the Ministry of Health 1 . Maranhão, in 2011, showed an overall detection rate of 56.0/100,000 inhabitants and was classified as a hyperendemic state.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of Phases I and II were published in the Journal of the Brazilian Society of Tropical Medicine 6,7 . This study was developed to determine the detection rate of leprosy in the general population, identify the clinical forms, examine the contacts, and treat the diagnosed cases.…”
Section: Resultsmentioning
confidence: 99%
“…In the City of Buriticupu the detection rate was 23.6 new cases per 10,000 inhabitants in the year 2000 and 27.4 per 10,000 in 2001 6,7 , thus motivating the development of the current research.…”
Section: Introductionmentioning
confidence: 92%